Design the Back-Up Line of Power Supply Automatic Fireplace Building in Angkasapura II Bandung - Putri Mariana; Rahmat Hidayat (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2022)
Angkasapura II is a State-Owned Enterprise (BUMN) that serves air traffic travel using airplanes which cannot be separated from the need for electricity. Almost all services use electricity, without exception the PKP-PK Building or the fire fighting building. This is because this building has an integrated fire detector that is connected from every room throughout the Angkasapura II area directly with the PKP-PK Building or the fire department building. The problem is because the PKP-PK power source is still sourced from the TNI AU base and has not been sourced from PT Angkasa Pura II. It is feared that if the main source of PKP-PK electricity is interrupted, there will no longer be a backup power supply in the PKP-PK area. From the results of this study, a backup power supply line for the PKP-PK area was made from Angkasapura II, with this if the main electricity had problems, the area could operate smoothly because it had been backed up by the electricity supply from PLN and the Angkasapura II Genset. .